Pengaruh Pemahaman Sistem Akuntansi, Pemanfaatan Teknologi Informasi dan Pengendalian Internal Terhadap Pengelolaan Anggaran Dana Desa - Mutiara Ratu Shapura,; Nurlaila Nurlaila,; Nurul Jannah, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Management of village fund management is accountability or answering and explaining the performance and actions of a person/leader of an organizational unit to parties who have rights or who are authorized to ask for accountability in the form of reports with the principle that every village financial management activity must be accountable to the village community. Research methods used The quantitative method used was a sample size of 34 people. The data collection instrument used was a questionnaire. The dependent variable of this research is village fund budget management and the independent variables are understanding the accounting system, use of information technology and internal control. The data analysis technique used is multiple linear regression analysis. The results of the t test show that (1) the variable understanding the accounting system has no effect on village fund budget management, the use of information technology has an effect on village fund budget management, internal control has a positive effect on village fund budget management while simultaneously the variables understanding the accounting system, use of information technology and internal control has a significant and positive effect on village fund budget management.